Ocular surface health and disease: insight from single-cell RNA sequencing - Ou, Shangkun; Cai, Minqing; Feng, Yuchong; Lin, Sijie; Zheng, Xueer; Zhao, Su; Gu, Hao; Wu, Yiming (Frontiers in Genetics, 2025)
Ocular surface tissues, primarily consisting of the cornea, meibomian glands, conjunctiva and lacrimal glands, are crucial components of the eyes and are in direct contact with external environment. Various ocular surface abnormalities can lead to ocular surface diseases, and in severe cases, blindness. The intricate diversity of cell types and states, along with the absence of definitive biomarkers for ocular surface tissues, has posed significant challenges to fully understanding corneal stability, disease mechanisms, and therapeutic development. Single-cell RNA sequencing (scRNA-seq) is an advanced analytical technique used to examine the transcriptomes of individual cells. It enables detailed analysis of complex cellular dynamics, the distinction of various cell types, and the discovery of new biomarkers, thus deepening our insight into diverse cellular behaviors. Currently, scRNA-seq is mainly applied to study the developmental processes of ocular surface cells and to explore the pathogenic mechanisms of related diseases, such as dry eye disease, pterygium, keratoconus, Fuchs corneal endothelial dystrophy, ocular graft-versus-host disease, and primary acquired nasolacrimal duct obstruction, which involve the cornea, conjunctiva, and lacrimal gland. This review summarizes the principles and applications of the scRNA-seq technique, including its mechanism, effects, limitations, and applications in ocular surface research, aiming to bridge the gap between incomplete understanding and rapid technological progress of scRNA-seq.